CIC: a radiation tolerant 65 nm data aggregation ASIC for the future CMS tracking detector at LHC. (1st February 2023) - Nodari, B.; Bergamin, G.; Caponetto, L.; Caratelli, A.; Ceresa, D.; Galbit, G.; Kloukinas, K.; Scarfi', S.; Viret, S.
Abstract: For the Phase II upgrade at HL-LHC, CMS needs a new Outer Tracker detector able to cope with reduced material budget, increased radiation tolerance and higher pile-up conditions with respect to LHC. The main feature of the Outer Tracker will be its inclusion at the first level of the CMS trigger system with data readout at 40 MHz. Two types of modules, Pixel-Strip and Strip-Strip will equip the Outer Tracker. Each module consists of a superposition of two silicon layers, able to detect charged particles, and an innovative readout electronics, allowing a significant data rate reduction. The Concentrator Integrated Circuit (CIC) is a 65 nm CMOS radiation tolerant front-end ASIC for both modules. It is considered a fundamental element of the future detector front-end chain due to its role in aggregating and compressing data from 8 front-end ASICs on each module. It reduces the data throughput by an order of magnitude. Two first version of the CIC were previously developed and tested. This paper will present the pre-production version, called CIC2.1, together with the functional and wafer test results.